Sick or Sad? A Qualitative Study on How Dutch GPs Deal With Sadness Complaints Among Young Adults - van Dijk, Eva L.; van Tol, Donald G.; Diemers, Agnes D.; Wienen, Albert W.; Batstra, Laura (Frontiers in Sociology, 2022)
Feelings of sadness among young adults related to a certain phase of life or to societal factors, run the risk of being interpreted as an individual medical problem. Therefore, healthcare professionals should more often widen their perspective and consider de-medicalization as being part of their professional responsibility too (RvS, 2017). This article presents results from a qualitative interview conducted with 13 GP’s in different phases of their career to get more insight into the way they deal with complaints of sadness among young adults. All participants acted proactively but in different ways. Based on the interviews a typology of three types of general practitioners has been created: the fast referrer, the expert and the societal GP. There seems to be a paradox in the way GPs think about de-medicalization on a macro level and the way they act on a micro level. Elaborating on Parsons (1951) classical concept of the sick role, this study introduces the term semi-legitimized sick role to clarify this paradox. The third type: ‘the societal GP’ appears to be the most able to show a more multifactorial view on complaints of sadness. Therefore, this type connects the most to a course of de-medicalization.